Optical link acquisition for the LISA mission with in-field pointing architecture. (June 2023) - Hechenblaikner, Gerald; Delchambre, Simon; Ziegler, Tobias
Abstract: We present a comprehensive simulation of the spatial acquisition of optical links for the LISA mission in the in-field pointing architecture, where a fast pointing mirror is used to move the line-of-sight of the optical transceiver, which was studied as an alternative scheme to the baselined telescope pointing architecture. The simulation includes a representative model of the far-field intensity distribution and the beam detection process using a realistic detector model, and a model of the expected platform jitter for two alternative control modes with different associated jitter spectra. For optimally adjusted detector settings and accounting for the actual far-field beam profile, we investigate the dependency of acquisition performance on the jitter spectrum and the track-width of the search spiral, while scan speed and detector integration time are varied over several orders of magnitude. Results show a strong dependency of the probability for acquisition failure on the width of the auto-correlation function of the jitter spectrum, which we compare to predictions of analytical models. Depending on the choice of scan speed, three different regimes may be entered which differ in failure probability by several orders of magnitude. We then use these results to optimize the acquisition architecture for the given jitter spectra with respect to failure rate and overall duration, concluding that the full constellation could be acquired on average in less than one minute. Our method and findings can be applied to any other space mission using a fine-steering mirror for link acquisition. Highlights: Link acquisition failure rates depend greatly on scan speed and jitter correlations. Beam profile, scan speed, and integration time affect SNR and detection radius. 3 acquisition regimes may be entered depending on scan speed, generally applicable. Full end-to-end simulations and analytical models optimize acquisition times. Optical link acquisition for constellation in less than one minute with in-field pointing.